The Influence of Location and Product Quality on Customer Loyalty at Toko Busana Ayu Cirebon - JULIANA, Aef Firman; SAHARA, Sahara; ANISA, Desty Cristya (International Journal of Environmental, Sustainability, and Social Science, 2025)
This study analyzes the influence of location and product quality on customer loyalty at Toko Busana Ayu Cirebon, a Muslim fashion MSME. In a competitive business landscape, understanding the factors driving customer loyalty is crucial. Using a quantitative method with a survey approach, 96 consumer respondents from Toko Busana Ayu in Cirebon were selected through purposive sampling. Primary data were collected via a Likert questionnaire, supported by secondary data. Data analysis involved validity, reliability, classical assumptions, multiple linear regression, coefficient of determination, and t- and F-tests. The results indicate that location and product quality, individually and simultaneously, have a positive and significant effect on customer loyalty. Partially, location (t=2.079; p=0.040) and product quality (t=9.528; p=0.000) significantly influenced loyalty. Simultaneously, both variables (F=78.080; p=0.000) were also significant. The coefficient of determination (R2) of 0.627 indicates that 62.7% of the variation in customer loyalty is explained by location and product quality. These findings emphasize the crucial role of strategic location and superior product quality in building customer loyalty among Muslim fashion MSMEs. This research contributes to the marketing and MSME literature, offering practical implications for business actors.